Collaborative filtering ambient preference of batik contemporary quality / Izyan Iryani Mohd Yusouf - Mohd Yusouf, Izyan Iryani (2006)
Collaborative filtering is the best method to predict the consumers of products by preserving the data of user system. Collaborative filtering is the database for web-based system as the database to retrieve back the data from the past consumers. It is t>eneficial for user of the system to find the preference products. The Objectives of this research are to identify an ambient perception on batik quality, to categorize an ambient selection of batik in terms of its quality and finally to propose a model of ambient perceives on batik quality as a review components of recommender system. There are several method used to collect the data and information needed in this research, primary and secondary resources are used in order to fulfill the research objectives. Primary data are collected through the distribution of questionnaire and interviews. While secondary data is taken from journals and internet resources. All the data gathered from this research were analyzed using SPSS 11.5 software, Microsoft Powerpoint to build the charts and Rational Rose to build the model. Data were presented in the form of frequency distribution tables for selected variables, and via graphical presentation like bar and pie charts.